Nilai Ekonomi Syariah sebagai Dasar Strategi Pemberdayaan Masyarakat - Fuaidi, Isyrokh (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
Discourse-related community empowerment remains increasingly important issue to which various concerning parties have always given serius attention in this regard including government, scholars, practitioners and the public in general. All strives to present an ideal concept regarding theories, insights, policies and implementations as empowerment strategy in building a society. The interesting aspect that still needs to be addressed in the discourse is related to the concept of empowerment strategies elaborated through Shariah economic values that will complement the spaces of community development atmospheres. This research uses a descriptive qualitative method with a literature study approach sourced from a review of journals and books that are relevant in the context of community empowerment. The results concludes that the implementation of community empowerment can be effectively implemented by applying the principles and values of sharia economics approach such as increasing professionalism (al-itqan) of human resources, promoting entrepreneurial culture, local wisdom-based management and strengthening philanthropy-based programs. By applying or at least promoting these values in order to become a shared consciousness among society, the community empowerment programs will be more effectively implemented.